Janus nanocarrier-based co-delivery of doxorubicin and berberine weakens chemotherapy-exacerbated hepatocellular carcinoma recurrence. (December 2019) - Zhang, Fan; Jia, Yong; Zheng, Xiao; Shao, Dan; Zhao, Yawei; Wang, Zheng; Dawulieti, Jianati; Liu, Wenliang; Sun, Madi; Sun, Wen; Pan, Yue; Cui, Lianzhi; et al.
Abstract: Despite the rapid progress which has been made in hepatocellular carcinoma (HCC) chemotherapeutics, recurrence of liver cancer still remains a barrier to achieve satisfying prognosis. Herein, we aimed to decipher the role of berberine (BER) in chemotherapy-exacerbated HCC repopulation via developing a nanocarrier co-deliveries doxorubicin (DOX) and BER to achieve a synergic effect in HCC treatment. The underlying fact of chemotherapy that promotes HCC repopulation was firstly examined and corroborated by clinical samples and murine repopulation model. Then, hyaluronic acid (HA)-conjugated Janus nanocarrier (HA-MSN@DB) was developed to load DOX and BER simultaneously. The HCC targeting efficiency, pH-controlled drug-release and anti-cancer property of HA-MSN@DB were assessed in CD44-overexpressed HCCs and normal liver cells. Magnet resonance imaging, bio-distribution, biocompatibility, tumor and recurrence inhibition studies were performed in H22 tumor-bearing mice. BER significantly reduced doxorubicin (DOX)-triggered HCC repopulation in vitro and in vivo through inhibiting Caspase-3-iPLA2-COX-2 pathway. The delivery of HA-MSN@DB into HCCs through CD44 receptor-mediated targeting effect was demonstrated. The controlled release of DOX and BER in response to acidic tumor microenvironment was validated. Importantly, HA-MSN@DB drastically enhanced the antitumor activity of DOX and suppressed DOX-exacerbated HCC repopulation in vitro and in vivo . Furthermore, HA-MSN@DB exhibited enhanced tumor accumulation and biocompatibility. Our findings revealed the pivotal role of BER in overcoming chemotherapy-exacerbated HCC repopulation through Caspase-3-iPLA2-COX-2 pathway, thereby providing a promising and stable nanocarrier integrating DOX and BER for effective HCC chemotherapy without repopulation. Statement of significance: In this work, we have first demonstrated the fact that berberine (Ber) reduces chemotherapy-exacerbated HCC recurrence and studied its mechanism by the aid of a doxorubicin-induced mice HCC relapse model. We then developed a promising strategy that simultaneously inhibits HCC and its recurrence with an HCC-targeted co-delivery nanocarrier HA-MSN@DB and revealed that such an inhibition was related with the suppression of Caspase-3-iPLA2-COX-2 pathway by berberine. Graphical abstract: Image, graphical abstract